A02 Natural History In Animal Models of HD; HD Recapitulation?. (17th September 2014) - Barker, R
Abstract : The genetic basis of HD means that it is relatively easy to make animal models that recapitulate the core genetic event, namely the CAG expansion in exon 1 of the huntingtin gene. This was achieved in the mid 1990s and replaced the previous models that essentially sought to mimic the core pathological event, namely the loss of striatal projection neurons using selective excitotoxic lesions. This new generation of transgenic models has provided great insight into the disease process especially at the molecular and cellular level, but what is less clear is what they have told us about the natural history of the clinical condition, which is well known to be very variable from patient to patient and for which the basis is unknown. In the clinic one has the advantage of asking patients and carers what the problems are and also studying them in detail over long periods of time using a range of different approaches. Obviously the ability to intervene and prove causal links in pathology and clinical features is not possible in patients in the way it is in animal models. Nevertheless the inability of animals to tell you their symptoms and our limited capacity to assess signs and problems in the cognitive, affective and metabolic realms limits what we can truly learn from animal models. This is especially true as they are bred to have a stereotypical clinical course in a way that is not seen in patients, who vary in the repertoire of clinical features they display as well as their rates of progression. Thus whilst these models can superficially resemble patients in some key areas, they miss many of the subtleties and complexities of human disease. In this talk I will attempt to highlight how animal models can help us understand the natural history of HD as well as their major shortcomings.